Unveiling the Power of Good Corporate Governance: The Key to Effective Zakat Administration - Keumala Ulfah, Almira; Razali, Ramadhan; Mohamed A. Ismail, Sherif (Filantropi : Jurnal Manajemen Zakat dan Wakaf, 2025)
This study aims to comprehensively analyze the implementation of Good Corporate Governance (GCG) in zakat administration to enhance transparency, accountability, and efficiency. As a country with a majority Muslim population, Indonesia has vast zakat potential, requiring professional management by zakat institutions. This research employs a qualitative methodology with a grounded theory approach to understand the complexities of zakat governance from a contextual perspective. The findings indicate that implementing GCG principles such as transparency, accountability, trustworthiness, responsibility, and fairnessis crucial for optimizing zakat management. Proper governance ensures that zakat institutions fulfill their obligations to both zakat payers (muzakki) and beneficiaries (mustahik). However, challenges such as weak supervision systems and potential misuse of zakat funds necessitate a structured governance framework. Thus, effective zakat administration should not rely solely on goodwill but must be supported by strong governance mechanisms to maximize social and economic impact.